Identifikasi Faktor Yang Mempengaruhi Keputusan Penggunaan Bank Digital Generasi Z Di Purwokerto - Sulasih Sulasih; Maulidha Tri Kurnia; Yans Nur Afifah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The study aims to examine the influence of three independent variables: digital literacy, brand image, and promotion on the decision to use Superbank. This study uses a quantitative approach with a survey method through a questionnaire distributed to 385 Generation Z respondents who are superbank users in Purwokerto. The sampling technique used purposive sampling with criteria such as age and use of superbank. Data were analyzed using classical assumption tests and multiple linear regression using SPSS version 26. The results showed that all three variables simultaneously had a significant effect on the decision to use. Partially, digital literacy and promotion had a positive and significant effect. Meanwhile, brand image did not have a significant effect. The insignificance of brand image is because superbanks are still relatively new and do not have strong differentiation. This generation is more driven by direct experience and practical value offered through promotions or service features, rather than solely brand image.